2016
DOI: 10.2105/ajph.2015.302981
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Transgender Veterans in US States With and Without Discrimination and Hate Crime Legal Protection

Abstract: Understanding lesbian, gay, bisexual, and transgender social stressors can inform treatment and care coordination for transgender populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 38 publications
4
77
0
2
Order By: Relevance
“…The applicability of these theories in explaining susceptibility to SI and SA has been supported by research in sexual minority populations in the United States and has recently been applied to the understanding of transgender suicide (Cochran, Balsam, Flentje, Malte, & Simpson, ; Lehavot & Simoni, ; Tebbe & Moradi, ; Testa et al., ). Initial support for this theory with transgender veterans living in states with employment protections against discrimination was demonstrated with a 43% less likelihood of self‐harm relative to veterans living in states without these protections (Blosnich et al., ). Moreover, Lehavot, Simpson, and Shipherd () found that self‐reported housing and employment discrimination, heterosexism, and shame related to transgender identity were positively associated with either or both past‐year SI and lifetime SA history among transgender veterans.…”
mentioning
confidence: 99%
“…The applicability of these theories in explaining susceptibility to SI and SA has been supported by research in sexual minority populations in the United States and has recently been applied to the understanding of transgender suicide (Cochran, Balsam, Flentje, Malte, & Simpson, ; Lehavot & Simoni, ; Tebbe & Moradi, ; Testa et al., ). Initial support for this theory with transgender veterans living in states with employment protections against discrimination was demonstrated with a 43% less likelihood of self‐harm relative to veterans living in states without these protections (Blosnich et al., ). Moreover, Lehavot, Simpson, and Shipherd () found that self‐reported housing and employment discrimination, heterosexism, and shame related to transgender identity were positively associated with either or both past‐year SI and lifetime SA history among transgender veterans.…”
mentioning
confidence: 99%
“…It is critical to understand that discrimination and discriminatory policies act as social determinants that infl uence health outcomes. A study that evaluated 1,640 Veterans with gender dysphoria found that those who resided in states with employment non-discrimination protection had a signifi cantly lower prevalence of mood disorders, self-injurious behavior, and suicidality (Blosnich et al, 2016).…”
Section: Gender Dysphoria In United States Veterans and Military Persmentioning
confidence: 99%
“…Discriminatory acts expose LGBT people to verbal harassment, physical violence, and, in the most extreme cases, death. 19 Discriminatory public policies—such as same-sex marriage bans 20 and lack of protections against hate crimes or employment-based discrimination at the state level 21 —have been associated with worse LGBT health outcomes. These effects are especially pronounced for transgender Americans.…”
Section: Discrimination and Stigmamentioning
confidence: 99%